Sistem Pengendalian Persediaan Stok Obat dengan Menggunakan Metode Analisis Always Better Control dan Metode Economic Order Quantity Pada Apotek - Shofika Adilya; Fitriani Muttakin; Angraini (STMIK Budi Darma, 2024)
XYZ Pharmacy is a pharmacy that specializes in the sale of prescription medications and exclusively accepts prescriptions from licensed physicians. Problems that arise include determining which drugs should be prioritized to reduce production costs which result in unstable drug stock supplies, and frequent excesses and shortages of drug stock due to delays in drug orders from suppliers. Therefore, it is necessary to apply a technique that makes it easier to control drug stock at XYZ Pharmacy, which aims to make it easier for XYZ Pharmacy to determine which drugs should be prioritized and manage drug stock control in the pharmacy. To overcome these problems effectively. ABC analysis of drugs in group A shows that there are 7 types of drugs which contribute 35.00% of total drug use, and generate total income of 67%. In group B there are 6 types of drugs which represent 30.00% of total drug use and generate total income of 23%. Finally, group C consists of 7 types of drugs which cover 35.00% of total drug use, and generate total revenue of 11%. Using the EOQ method, analysis was carried out on 7 types of drugs in group A, obtaining various optimal order quantities EOQ. The highest EOQ was 90.64 or 90 items for OB2 drugs, while the lowest EOQ was 43.29 or 43 items for OB19. Each type of drug has a range of 1-4 Safety Stock, and the Reorder Point for each type of drug varies in terms of the number of units needed.